One “Two” Many: An Examination of Solo Perpetrator Versus Team Perpetrator Serial Homicides - Chai, April Miin Miin (Homicide studies, 2022)
The current study examines the offender, victim, and crime characteristics between solo perpetrators and team perpetrators of serial homicide. Cases on 1,137 solo perpetrators and 254 team perpetrators were collected from the Consolidated Serial Homicide Offender Database. Results showed team perpetrators were more likely to be older than those who committed serial homicides alone. Offenders who never confessed their crimes were less likely to participate in teams. In terms of victim and crime characteristics, team perpetrators were more likely to target employees or customers, have a lower victim count, and were more likely to exhibit sadistic behaviors compared to solo perpetrators. Theoretical and practical implications from this study are discussed.